Strategi Komunikasi Arja Muani Akah Canging Sebagai Hiburan Inovatif Di Desa Munggu Kecamatan Mengwi Kabupaten Badung - Ni Luh Putu Indah Purnama Dewi; I Wayan Wastawa; Ni Made Yuliani (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
One of the performances in Bali that is often performed is the arja dance drama, but in this millennial era, interest in arja drama dances has begun to decline. Arja is known as a classic theater with long and boring performances. The communication strategy was used by the Arja Muani Akah Canging group as an effort to attract the interest of the audience, from young to old. Arja muani Akah Canging provides a new atmosphere in presenting his show as innovative entertainment. The problems raised in this research are (1) what is the communication strategy of arja muani Akah Canging as innovative entertainment in Munggu Village, Mengwi sub-district, Badung regency? (2) what is the function of the communication strategy in staging arja muani Akah Canging as innovative entertainment in Munggu village, Mengwi sub-district, Badung district? (3) what are the implications of the arja muani Akah Canging communication strategy as innovative entertainment in Munggu village, Mengwi sub-district, Badung district? This study uses three theories to dissect the formulation of the problem, namely: the theory of turgi drama, the theory of structural functionalism communication, and the theory of rhetoric. This research uses qualitative methods by collecting data through observation, interviews, and literature studies. This study aims to examine the communication strategy arja muani Akah Canging as innovative entertainment. Based on the results of the study, this study found the following results: 1) The process of staging arja muani Akah Canging with the preparation, staging, final staging stages. As well as a communication strategy in staging the arja muani Akah Canging in Munggu village, Mengwi sub-district, Badung district. 2) The function of staging arja muani Akah Canging is the primary function as a means of entertainment for the community in religious ceremony activities.